2023
DOI: 10.1096/fj.202201713r
|View full text |Cite
|
Sign up to set email alerts
|

Food safety in vulnerable populations: A perspective on the challenges and solutions

Abstract: World Health Organization (WHO) 1 reports that unsafe food leads to foodborne disease and malnutrition especially in neonates, children, the aged, and the ill. The WHO report revealed that about thirty-one foodborne hazards were responsible for foodborne diseases affecting about 600 million people with an accompanying 420 000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A similar risk-based approach may also be adopted during inspections such that the preparation of higher-risk foods or food operations catering to vulnerable communities be more closely observed and immediate guidance be provided, should food safety measures be found lacking, or should reluctance to practice safe measures be perceived among food handlers. It has been shown that a food safety regimen guided by food type, process controls and intended population could mitigate or reduce food-safety risks [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar risk-based approach may also be adopted during inspections such that the preparation of higher-risk foods or food operations catering to vulnerable communities be more closely observed and immediate guidance be provided, should food safety measures be found lacking, or should reluctance to practice safe measures be perceived among food handlers. It has been shown that a food safety regimen guided by food type, process controls and intended population could mitigate or reduce food-safety risks [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterials have ushered in a new era in food packaging technology, offering innovative solutions to the challenges faced by food rescue and humanitarian relief initiatives. By leveraging the unique properties of nanomaterials, the food industry can develop packaging systems that enhance food safety, prolong shelf life, and promote sustainability [49]. As ongoing research continues to explore novel applications of nanotechnology in food packaging, the potential for improving the efficiency and effectiveness of food rescue efforts remains promising.…”
Section: Sustainability and Environmental Impactmentioning
confidence: 99%
“…Vulnerable populations, such as those in remote and underserved communities, often face significant obstacles in accessing safe and nutritious food. The food environment in these regions is characterized by the limited availability of fresh produce, inadequate sanitation, and poor education and training on food safety, leading to heightened food safety risks [49]. Additionally, vulnerable populations are more susceptible to becoming food insecure or worsening their food security in the face of shocks, such as crop failures, loss of income, or sudden health crises, and have fewer coping strategies to deal with these shocks.…”
Section: Nanoengineering and Food Security Challenges In Vulnerable R...mentioning
confidence: 99%